INTRODUCTION TO VARIOUS KINDS OF LEARNING METHODS AND MODELS AND THEIR IMPLEMENTATION IN LEARNING IMPLEMENTATION PLANS (RPP) AT SMP N 38 PADANG - vivi fitriani; Diana Susanti; Liza Yulia Sari (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2023)
ABSTRACTThere are various preparatory activities that must be carried out by the teacher before starting the learning process such as preparing a lesson plan (RPP). this is done so that what is the target and priority of the teacher in teaching is fulfilled by students. At SMP N 38 Padang, teachers have been equipped with various learning methods and models. However, sometimes its application in RPP cannot be applied as fully as possible. Teachers only use certain methods and models even though there are many learning methods and models that teachers can use in learning for different materials. Seeing these conditions, it is necessary to do teacher service regarding the introduction of learning methods and models and their implementation in lesson plans at SMPN 38 Padang.Keyword: Learning Methods,  Models, Learning Implementation Plans